2022
DOI: 10.3390/en15093194
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the Effect of Nozzle on Underwater Detonation Shock Wave and Bubble Pulsation

Abstract: The subject of a gas jet generated by underwater detonation is an important issue in the field of underwater propulsion. The experimental system of underwater detonation is established, which utilizes a high-speed camera to record the morphological changes in bubbles and various pressure sensors to measure the flow field pressure. The effect of nozzles and the pressure of the flow field are analyzed thoroughly. The comparison of the bubble and field pressure shows that the shrinking nozzle increases the peak p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…Thereafter, a larger bubble with a diameter of d ≈3.5 mm exploded with a time delay (frame 6), despite it being subjected to shock compression earlier, being somewhat upstream with respect to the two bubbles that exploded earlier. Furthermore, this bubble expanded (frame 7), shrank again (frame 8) and expanded again (frames 9-11), taking the shape of a parachute (frames 12-14), and then broke up into small fragments (frames [15][16][17][18][19][20]. The processing of video records made it possible to gain information on the shockinduced motion of individual bubbles behind the traveling SW.…”
Section: Single Shock Wave Propagation In Bubbly Watermentioning
confidence: 99%
See 1 more Smart Citation
“…Thereafter, a larger bubble with a diameter of d ≈3.5 mm exploded with a time delay (frame 6), despite it being subjected to shock compression earlier, being somewhat upstream with respect to the two bubbles that exploded earlier. Furthermore, this bubble expanded (frame 7), shrank again (frame 8) and expanded again (frames 9-11), taking the shape of a parachute (frames 12-14), and then broke up into small fragments (frames [15][16][17][18][19][20]. The processing of video records made it possible to gain information on the shockinduced motion of individual bubbles behind the traveling SW.…”
Section: Single Shock Wave Propagation In Bubbly Watermentioning
confidence: 99%
“…In [17], the results of experimental study on gas jetting by an underwater detonation tube were reported, and the mechanism of shock wave propagation and bubble deformation was discussed. The effect of the nozzle attached to a detonation tube on the underwater SW and gas detonation bubble was investigated in [18]. Three types of nozzles (converging, straight, and diverging) were examined.…”
Section: Introductionmentioning
confidence: 99%
“…Wang et al [28] reported the results of numerical simulation and experimental study on gas jetting by an underwater DT and discussed the mechanism of shock wave propagation and bubble deformation. Wang et al [29] investigated both computationally and experimentally the effect of the nozzle attached to a DT on the underwater shock wave and gas detonation bubble. Three types of nozzles (converging, straight, and diverging) were examined.…”
Section: Introductionmentioning
confidence: 99%